Low pay as an alternative to public direct job creation? Lessons from the German case - Werner Eichhorst (Institute for the Study of Labor (IZA), 2015)
This contribution draws some conclusions from the experience of attempts by the German government at integrating the most vulnerable groups into the labor market, in particular the long-term unemployed and the low skilled. There has been a sort of paradigm shift that goes beyond active labor market policies and public direct job creation in favor of allowing for a more flexible labor market to emerge, thus implying a growing low-pay sector. This policy reversal can be seen as a partial success as those that were formerly excluded now have a somewhat better access to the labor market. However, this improved access comes with some limitations in terms of the quality of jobs and with respect to the upward mobility of those who enter the labor market at low-pay levels.
Keywords: J64; J65; J68; 330; direct job creation; low pay; subsidized employment; evaluation; Germany